Wunder auf dem Weg durch die Wüste. Israels Verwandlung zum Ort der Gegenwart JHWHs in Ps 114 - Siquans, Agnethe (Protokolle zur Bibel, 2012)
Psalm 114 tells the story of Israel’s transformation into YHWH’s sanctuary, the place of his presence in the world. Time and especially space are also transformed: What happened once in the past, may happen time and again. As for space, the land is an important feature, but YHWH’s presence is bound to Israel, his people. Strikingly - especially in comparison to some biblical intertexts -, the temple or Jerusalem are not mentioned in the psalm. The sanctuary is where Israel is, not only within the land, but also in the diaspora.